2007
DOI: 10.1111/j.1467-9906.2007.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Action Research for Environmental Health: Encountering Freire in the Urban Barrio

Abstract: The community-based approach to health research and intervention is a model of inquiry rooted in Freire's participatory action research (PAR). We need to show, in concept and practice, what it is about PAR that may be well suited for the types of health issues we encounter in inner-city environments. What type of learning results, how does this respond to particular health issues in the urban context, and what are the particular challenges faced in translating Freire's model into today's urban setting?To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The research outcomes are often designed to develop research or other skills in the community of practice, so that they may continue to conduct their own research (Gibson-Graham, 1994). Other outcomes of PAR include for example, policy changes, institutional change, building social capital and improving health (Gatenby and Humphries, 2000;Mama, 2000;Gonzalez et al, 2007). Variations of PAR, such as participatory rural appraisal have also been used in rural development to work with small farmers in developing countries (Chambers, 2005).…”
Section: Rationale For Participatory Action Researchmentioning
confidence: 98%
“…The research outcomes are often designed to develop research or other skills in the community of practice, so that they may continue to conduct their own research (Gibson-Graham, 1994). Other outcomes of PAR include for example, policy changes, institutional change, building social capital and improving health (Gatenby and Humphries, 2000;Mama, 2000;Gonzalez et al, 2007). Variations of PAR, such as participatory rural appraisal have also been used in rural development to work with small farmers in developing countries (Chambers, 2005).…”
Section: Rationale For Participatory Action Researchmentioning
confidence: 98%
“…As anecdotal evidence of this, simply imagine the very different reactions people of divergent ideological-political allegiances display when shown a chart of carbon dioxide measurements over time from the Mauna Loa observatory. Examples of context-centered research include efforts to understand how communities interpret the idea of "neighborhood" and its implications for community life (Hipp et al 2011), how place attachment affects environmental behavior (Ogunseitan 2005), or how participatory action research complements technical knowledge (e.g., González et al 2007). By being open to the everyday experience of subjects, the socialecological frame coheres well with action-research as a mode of participative-collaborative inquiry.…”
Section: Core Principles Of Social Ecologymentioning
confidence: 99%
“…see Greiving et al 2006). Yet another promising area of study is how to couple these analytics with community-based processes (Gonza´lez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As an example of the complex health effects of urban form, researchers have recently become concerned over so-called urban street canyons (Zhou andLevy 2008, Mead 2008), which are created by high-rise condominium or commercial buildings lining both sides of arterial streets and causing high concentrations of vehicular particulates to build up. As another example, Gonza´lez et al (2007) found that, contrary to the often-assumed contention that most of the air toxics risk in Southern California originates from vehicular emissions from the freeway, in some parts of the region, the problem of many, small point sources deeply embedded in the fabric of the neighbourhood, can bring about risk hotspots. This phenomenon, which we will refer to as urban saturation, arises because many small point sources remain 'under the radar' of regulatory programmes, since their VOC (volatile organic carbon) emissions fall under reporting thresholds, such as the Toxics Release Inventory.…”
Section: Introductionmentioning
confidence: 86%